Superfine grinding pretreatment enhances emulsifying, gel properties and in vitro digestibility of laccase-treated α-Lactalbumin. (1st March 2022) - Hu, Jialun; Ma, Ling; Liu, Xianqi; Li, Hongyu; Zhang, Minghan; Jiang, Zhanmei; Hou, Juncai
Abstract: The main purpose of this study was to confirm the impact of superfine grinding treatment on physicochemical, functional properties and in vitro digestibility of laccase-treated α-Lactalbumin (α-Lac). With the grinding time ranging from 0 to 12 h, the high molecular weight polymers, relative dityrosine and surface hydrophobicity of laccase-treated α-Lac increased significantly ( P ＜ 0.05). After superfine grinding treatment (12 h), compared with α-Lac, the emulsifying activity and emulsifying stability of laccase-treated α-Lac were increased by 24.78% and 10.50%, and its gel strength and water holding capacity were enhanced by 19.92% and 21.78%. In addition, superfine grinding treatment reduced α-helix and β-sheet content, and increased β-turns and random coils of α-Lac and laccase-treated α-Lac. Furthermore, the in vitro digestibility of α-Lac and laccase-treated α-Lac was improved by 5.77% and 4.47% in intestine after treated by superfine grinding for 12 h. These results indicated that combination treatment of superfine grinding and laccase could promote the crosslinking of α-Lac and improve its emulsifying, gel properties and in vitro digestibility. Highlights: Superfine grinding promoted the degree of laccase crosslinking α-Lactalbumin (α-Lac). Superfine grinding improved the emulsifying and gel properties of laccase-treated α-Lac. Superfine grinding changed the in vitro digestibility of laccase-treated α-Lac.